COMPETITIVE POTENTIAL OF FUNCTIONAL ENRICHED BAKERY PRODUCTS - E. P. Victorova; O. V. Fedoseyeva; T. A. Shakhrai; N. N. Kornen (Новые технологии)
The article presents the results of assessing the competitive potential of enriched functional bakery products. Developments in the field of creating functional enriched food products are a priority area that allows implementing the concept of healthy nutrition of the population of the Russian Federation because their consumption will ensure normal nutritional status due to macro- and micronutrients. A comprehensive indicator namely, its competitive potential, along with quality, safety, nutritional value, and preservation characteristics is of particular importance when producing the developed product.The competitive potential of a functional bakery product has been evaluated by five groups of indicators: functional efficiency; safety; standardization; reliability; patent law, in comparison with the basic unenriched bakery product, considered as the standard. An analysis of the evaluation results shows that the competitive potential of the developed bread exceeds this indicator for the base product by 1.6 times, due to the fact that the developed bread is characterized by a higher indicator of functional efficiency, especially according to the content of dietary fiber (Qrel = 9.105), copper (Qrel = 2,667), phosphorus (Qrel = 1,694), potassium (Qrel = 1,445) and the range of functionality (Qrel = 1,5). In addition, the patent legal indicator and the reliability indicator of the developed functional bread enriched with «Grushevaya» food supplement exceed the base product (Qrel = 2.0) and (Qrel = 1.5), respectively. It has been shown that the competitive potential of the developed bread exceeds this indicator for the base product is almost 2 times, since it is characterized by a higher indicator of functional efficiency, especially according to the content of dietary fiber (Qrel = 13,500), copper (Qrel = 4,500), phosphorus (Qrel = 1,932), potassium (Qrel = 1,676) R-active substances (Qrel = 1.275) and the range of functionality (Qrel = 1.5). It should be noted that the patent-legal indicator and the reliability indicator of functional buns enriched with Grushevaya food supplement also exceed the base product (Qrel = 2.0) and (Qrel = 1.5), respectively. Thus, it has been found that the competitive potential of the developed functional bakery products (bread and rolls), enriched with Grushevaya food supplement, is significantly higher than the competitive potential of the basic products – bread and rolls.